Phase change energy storage material giving consideration to high-temperature heat storage and low-temperature cold storage and preparation method of phase change energy storage material
Through the combination of paraffin, liquid water and surfactant, phase change energy storage materials in the form of paraffin water-in-paraffin emulsion are formed, which solves the problem that the existing technology cannot meet the needs of high-temperature and low-temperature energy storage at the same time, and achieves efficient heat and cooling Can be comprehensively utilized.
Patent Information
- Application Number
- CN202411126108.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-02-25
AI Technical Summary
Existing phase change energy storage materials usually only work within a specific temperature range and cannot meet the energy storage needs of both high and low temperatures.
A phase change energy storage material in the form of a paraffin-based emulsion is formed by a specific preparation method using a combination of paraffin-based phase change material, liquid water and oil-soluble surfactant.
It realizes the functions of taking into account high-temperature heat storage and low-temperature cold storage, makes full use of the latent heat of phase transformation of paraffin and water, and improves the comprehensive utilization efficiency of energy.
Smart Images

Figure CN119505816A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage material production and application, and specifically relates to a phase change energy storage material capable of storing both high-temperature heat and low-temperature cold, and a preparation method thereof. Background Art
[0002] With the continuous increase in global energy consumption and the increasing dependence on renewable energy, efficient energy storage technology has become crucial. Among the various forms of energy storage, heat storage can achieve large-scale storage of energy, and the loss in the energy conversion process is relatively small. Therefore, heat storage has become an efficient, reliable and stable form of energy storage. According to different methods, heat storage can be divided into sensible heat storage, chemical heat storage and phase change heat storage. Among them, phase change energy storage materials are materials that use the property of substances to absorb or release a large amount of heat during phase change to achieve energy storage and release. Compared with traditional energy storage methods (such as batteries), phase change energy storage materials have the advantages of high energy storage density, small temperature change, and relatively stable energy storage and release processes. They show good application prospects in the fields of waste heat recovery, solar energy utilization, building energy conservation, and electric vehicle battery thermal management.
[0003] However, existing phase change energy storage materials can only function within a specific temperature range, focusing on either high-temperature heat storage or low-temperature cold storage. In the face of periodic hot and cold changes in equipment or ambient temperature, they cannot meet the energy storage needs of both high and low temperatures. For example, some inorganic salt phase change materials have a high phase change temperature and are suitable for high-temperature heat storage, but they perform poorly at low temperatures; and some organic compounds have good cold storage performance at low temperatures, but are easily decomposed or their performance decays at high temperatures.
[0004] Therefore, there is an urgent need to design a phase change material that can store and release both heat and cold energy at the same time, so as to achieve the dual utilization of heat energy and cold energy. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage, which comprises, by mass percentage, 65-89wt.% of paraffin-based phase change material, 10-30wt.% of liquid water phase, and 1-5wt.% of oil-soluble surfactant.
[0008] As a preferred solution of the phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage as described in the present invention, the paraffin-based phase change material includes normal alkane paraffin, isoalkane paraffin or a mixture of normal and isoparaffins with different carbon chain lengths.
[0009] As a preferred solution of the phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage as described in the present invention, the oil-soluble surfactant includes one or more of Span60, Span80, and glyceryl monostearate.
[0010] As a preferred solution of the phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage as described in the present invention, the phase change temperature of the paraffin-based phase change material from solid to liquid is 35-40°C, and the phase change latent heat is 155-165 kJ / kg.
[0011] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage.
[0012] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0013] The paraffin-based phase change material is heated to 70-75°C and then kept at a constant temperature for 20-40 minutes until the solid paraffin is completely melted, and then a surfactant is added and heated for 5-15 minutes to obtain a mixed liquid paraffin;
[0014] The paraffin-based phase change material is heated to 70-75° C. and then kept at a constant temperature for 20-40 minutes. After the material is completely melted, a surfactant is added and the material is heated for 5-7 minutes to obtain a liquid mixture.
[0015] After the liquid mixture is stirred at a speed of 200 to 250 r / min and cooled to 50±1°C, deionized water is added and the stirring speed is adjusted to 600 to 700 r / min to promote the dispersion of the water phase into micro-nano-scale water droplets in the liquid paraffin. After the water phase is added, the mixture is stirred for 10 to 12 minutes;
[0016] After the stirring is completed, the temperature is cooled down and the paraffin is completely solidified, and finally a phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage is obtained.
[0017] As a preferred embodiment of the method for preparing the phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage of the present invention, the method of adding water to the liquid paraffin is a combination of dripping and emulsification, including:
[0018] Divide the water into 4 to 6 equal portions by volume, take one portion and slowly add it dropwise into the paraffin. After the addition is completed, allow the water phase to fully emulsify in the liquid paraffin for 1 to 2 minutes. Repeat this process until the water sample is completely added to the liquid paraffin.
[0019] As a preferred embodiment of the method for preparing the phase change energy storage material capable of storing both high-temperature heat and low-temperature cold, the liquid paraffin is kept in a stirring state during the dropping and emulsifying process.
[0020] As a preferred embodiment of the method for preparing the phase change energy storage material capable of storing both high-temperature heat and low-temperature cold, the liquid paraffin is kept in a stirring state during the dropping and emulsifying process.
[0021] As a preferred embodiment of the method for preparing the phase change energy storage material capable of storing both high-temperature heat and low-temperature cold, the temperature of the deionized water is consistent with that of the liquid mixture.
[0022] As a preferred solution of the method for preparing the phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage as described in the present invention, wherein: the cooling temperature is 25±0.5°C.
[0023] Beneficial effects of the present invention:
[0024] (1) The present invention provides a phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage. Compared with the traditional phase change material that can only meet the needs of high-temperature heat storage or low-temperature cold storage, the present invention fully utilizes the phase change latent heat of paraffin and water, realizes the comprehensive utilization of both heat and cold energy, and enriches the levels and methods of energy storage and utilization.
[0025] (2) Considering that the ambient temperature of the materials is mostly at room temperature, paraffin is solid at room temperature and water is liquid, the phase change energy storage material prepared for both high-temperature heat storage and low-temperature cold storage is in the form of paraffin-water emulsion to form a solid mixture for easy transportation and storage.
[0026] (3) Since the water phase is emulsified into micro-nano droplets by surfactants, the crystallization supercooling of the water droplets is relatively large, that is, the water crystallization temperature drops from 0°C to below 0°C, resulting in a delayed response of the material to low-temperature cold storage. Therefore, the water content of the phase change energy storage material is adjusted and the type of surfactant is changed to improve the water crystallization supercooling phenomenon. The use of surfactants such as Span60 and glyceryl monostearate significantly increases the crystallization temperature of the water phase, while the high water content of 20 and 30wt.% significantly increases the energy storage density of the material in the cold storage process. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:
[0028] Figure 1 It is a product schematic diagram of a phase change energy storage material provided by the present invention that takes into account both high-temperature heat storage and low-temperature cold storage.
[0029] Figure 2 2 is a microscopic morphology of the phase change energy storage material observed under a polarizing microscope, wherein 201 is dispersed water droplets formed by emulsification, and 202 is wax crystals.
[0030] Figure 3 The temperature change curves of high temperature heat storage and heat release experiments of Examples 1, 2, and 3.
[0031] Figure 4 The temperature change curves of the low-temperature cold storage and cold release experiments of Examples 1, 2, and 3 are shown.
[0032] Figure 5 The temperature change curves of high temperature heat storage and heat release experiments of Examples 1, 4, and 5.
[0033] Figure 6 The temperature change curves of the low-temperature cold storage and cold release experiments of Examples 1, 4, and 5. DETAILED DESCRIPTION
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0036] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0037] The raw materials used in the present invention are all commercially available unless otherwise specified.
[0038] Example 1
[0039] This embodiment provides a method for preparing a phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage, specifically:
[0040] (1) Place 78 wt.% paraffin wax with a phase change temperature of 40°C in a high-temperature heating box, heat to 75°C and keep the temperature constant for 30 minutes, then add 2 wt.% of surfactant Span80 and continue heating for 10 minutes.
[0041] (2) Place the paraffin wax and Span80 mixture on a heated stirring table, stir at 200 r / min and cool to 50°C; add 20 wt.% of deionized water at 50°C into the liquid phase, adjust the stirring speed to 600 r / min, divide the deionized water into 5 equal volumes, take 1 portion and drop it into the liquid paraffin. After the addition is completed, continue to stir and emulsify for 1 minute to promote the dispersion of the water phase into micro-nano-scale water droplets in the liquid paraffin. The subsequent 4 portions of water phase are added in the same way of combining addition and emulsification. After the addition of the water phase is completed, continue to stir the mixed liquid for 10 minutes.
[0042] (3) After the stirring is completed, the emulsion is placed in a 25°C constant temperature box to cool down until the paraffin is completely solidified, and finally a phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage is obtained.
[0043] Figure 1 This is a product schematic diagram of the phase change energy storage material obtained in Example 1 of the present invention. Figure 2 This is a microscopic morphology of the phase change energy storage material under polarizing microscope observation. It can be seen from the figure that the phase change energy storage material is a milky white solid at the macro level, and flaky wax crystals (202) and round water droplets (201) dispersed in the wax crystals can be seen at the micro level. The two phase change materials are evenly distributed.
[0044] Example 2
[0045] The difference between this embodiment and embodiment 1 is that the type of surfactant is adjusted to Span60, and the rest of the preparation process is the same as that of embodiment 1 to obtain a phase change energy storage material.
[0046] Example 3
[0047] The difference between this embodiment and embodiment 1 is that the type of surfactant is adjusted to glyceryl monostearate, and the rest of the preparation process is the same as that of embodiment 1 to obtain a phase change energy storage material.
[0048] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 1.
[0049] Table 1
[0050]
[0051] High temperature heat storage process: Figure 3 The temperature change curves of high temperature heat storage and heat release experiments of Examples 1, 2, and 3 are shown in the table above. It can be seen from the table that the heat storage process of the phase change energy storage material at 25°C to 60°C is divided into three stages:
[0052] (1) When the temperature rises rapidly from 25°C to 35°C, the paraffin wax has not yet undergone phase change and absorbed heat;
[0053] (2) At 35°C to 40°C, the temperature rise curve becomes gentle, indicating that the paraffin begins to melt at this time, and absorbs a large amount of heat from the solid phase to the liquid phase, which delays the temperature rise of the material. The material exhibits the ability to store heat, and the heat is stored in the material in the form of the latent heat of the phase change of the paraffin. In this heat storage process, the endothermic phase change durations of Examples 1, 2, and 3 are 26 min, 22 min, and 23.5 min, respectively.
[0054] (3) At 40℃~60℃, the paraffin wax has completely melted and the temperature of the material rises rapidly, indicating that the material cannot continue to control the temperature without the paraffin wax absorbing heat and melting.
[0055] The cooling and heat release process from 60℃ to 25℃ is also divided into three stages:
[0056] (1) 60℃~40℃, the temperature drops rapidly, at this time the paraffin is liquid and has not yet solidified;
[0057] (2) 40℃~35℃, the cooling process is slow. At this time, the paraffin phase changes and releases heat, releasing the heat absorbed during high-temperature heat storage, delaying the temperature drop of the material. The heat is utilized through endothermic melting and exothermic solidification. In this exothermic process, the exothermic phase change time of Examples 1, 2, and 3 is 82 minutes.
[0058] (3) 35℃~25℃, the paraffin has solidified, and the temperature of the phase change material gradually decreases to the same temperature as the constant temperature box.
[0059] Low temperature cold storage process: Figure 4 The temperature change curves of the low-temperature cold storage and cold release experiments of Examples 1, 2, and 3 are shown in the table above. It can be seen from the table that the energy storage materials prepared by the surfactants of Examples 1, 2, and 3 have a cooling and cold storage process of 25°C to -20°C, which is divided into three stages:
[0060] (1) 25°C to 0°C, the temperature of the energy storage materials prepared from Span60 or glyceryl monostearate in Examples 2 and 3 drops rapidly, and the aqueous phase is in liquid state and has not reached the phase transition temperature. However, in Example 1, the phase change energy storage material prepared from Span80 has a corresponding rapid temperature drop interval from 25°C to -8.4°C;
[0061] (2) 0℃~0℃, the water droplets in the phase change energy storage materials of Examples 2 and 3 undergo phase change, and the water crystals release a large amount of phase change latent heat, so that the material remains at 0℃ and no longer decreases. At this time, the coldness of the environment is stored in the phase change material through water freezing; and the corresponding Example 1, the phase change material prepared by Span80 undergoes water crystallization phase change in the temperature range of -8.4℃~-8.4℃, which indicates that the water crystallization of the emulsion prepared by Span80 is supercooled, that is, there is a lag in the water phase freezing and cold storage process. The occurrence of this supercooling behavior is closely related to the type of surfactant. Span60 and glyceryl monostearate form crystals during the cooling process, adsorb on the surface of water droplets, become nucleation sites for water crystallization, and promote water crystallization and cold storage, while Span80 is not a crystal and cannot become a nucleation site to promote water crystallization, resulting in supercooling of water droplets; although the energy storage material prepared by Span80 exhibits water crystallization supercooling, Figure 4 It can be found that in Example 1, the cold storage time of Span80 (i.e., the time from -8.4°C to a maximum of -5.5°C and then down to -8.4°C) is 16 minutes, while the cold storage time (the time to maintain 0°C) of Examples 2 and 3 is only 7.5 minutes and 9 minutes, respectively. This shows that although there is a certain degree of supercooling in Example 1, that is, there is a lag in the cold storage temperature in response to cold energy, it is precisely because Span80 itself cannot become a water crystallization nucleation site, resulting in a slow water crystallization cold storage rate in the energy storage material, and the entire cold storage time is significantly longer than that of Examples 2 and 3. This is important for units or equipment that need to be insulated with the help of phase change energy storage materials. For example, under low temperature conditions in winter, electric vehicle batteries can extend the battery insulation time with the help of the heat released during the cold storage process of energy storage materials such as Example 1 to avoid the battery from cooling down too low a temperature quickly. Therefore, taking into account the above-mentioned cold storage temperature, cold storage time, etc., Example 1 is still the potential best sample.
[0062] In addition, although the differences in the temperature and duration of heat storage and cold storage in Examples 2 and 3 prepared by Span60 and glyceryl monostearate are very small, the melting point of glyceryl monostearate (75°C-78°C) is higher than that of Span60 (54-57°C). During the experiment, the paraffin was heated to 75°C to ensure that glyceryl monostearate could melt and dissolve in the liquid paraffin. It was observed in the experiment that when the temperature was lowered to 50°C, the entire solution was still transparent and not turbid, and no solid was precipitated, indicating that 2wt.% glyceryl monostearate can be fully dissolved in the paraffin after cooling. Therefore, from the perspective of the convenience of preparing energy storage materials, the preparation temperature of Span60 can be lower than that of glyceryl monostearate, which saves more heat.
[0063] (3) 0℃~-20℃, the water phase crystallization cold storage process in the phase change energy storage materials of Examples 2 and 3 has been completed, and the phase change materials continue to cool down to the ambient temperature of -20℃. The phase change material prepared by Span80 cools down from -8.4℃ to -20℃.
[0064] The process of heating and cooling from -20℃ to 25℃ is divided into three stages:
[0065] (1) -20°C to 0°C, the temperature of the phase change energy storage materials of Examples 1, 2, and 3 all rises rapidly, and the ice formed by cold storage does not melt and release cold;
[0066] (2) 0℃~0℃. Similar to supercooling, the phase change energy storage materials prepared by the three different surfactants all showed ice melting endothermic phenomenon at 0℃. At this time, the temperature of the material no longer changed, which was manifested as the cold energy stored in water crystals being released to the environment. During the cooling process, Span80 did not show a phase change temperature different from that of Span60 or glyceryl monostearate. In this cooling process, the cooling phase change duration of Examples 1, 2, and 3 was basically the same, about 15 minutes.
[0067] (3) 0℃~25℃, after the water phase cold storage is completely released, the temperature of the material continues to rise until it reaches the same as the ambient temperature of 25℃.
[0068] Example 4
[0069] The difference between this embodiment and embodiment 1 is that the addition amount of deionized water is adjusted to 10 wt.%, and the rest of the preparation process is the same as that of embodiment 1 to obtain a phase change energy storage material.
[0070] Example 5
[0071] The difference between this embodiment and embodiment 1 is that the addition amount of deionized water is adjusted to 30 wt.%, and the rest of the preparation process is the same as that of embodiment 1 to obtain a phase change energy storage material.
[0072] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 2.
[0073] Table 2
[0074]
[0075]
[0076] High temperature heat storage process: Figure 5The temperature change curves of high temperature heat storage and heat release experiments of Examples 1, 4, and 5 are shown in the table above. It can be seen that the energy storage materials of Examples 1, 4, and 5 with different moisture contents of 10, 20, and 30 wt.% are similar to those of Examples 1, 2, and 3, that is, the heat storage process of 25°C to 60°C is divided into three stages:
[0077] (1) 25℃~35℃, the temperature rises rapidly, but the temperature does not reach the paraffin phase transition temperature;
[0078] (2) At 35°C to 40°C, the temperature rise curve becomes gentle, and the paraffin undergoes a phase change from solid to liquid. The latent heat of the phase change absorbs the heat transferred from the environment, significantly delaying the temperature rise of the material, and the material exhibits the ability to store heat. In this heat storage process, since the wax contents of Examples 1, 4, and 5 are 78wt.%, 88wt.%, and 68wt.%, respectively, the difference in wax content leads to different amounts of paraffin participating in the endothermic phase change, which is manifested as a difference in the endothermic duration. The endothermic durations of the three are 26min, 36min, and 18min, respectively.
[0079] (3) At 40℃~60℃, the paraffin wax has completely melted and the temperature of the material rises rapidly, indicating that without the paraffin wax absorbing heat and melting, the material can no longer absorb heat and loses its temperature control effect.
[0080] The cooling and heat release process from 60℃ to 25℃ is also divided into three stages:
[0081] (1) 60℃~40℃, the temperature drops rapidly, at this time the paraffin is still in liquid phase and has not yet solidified;
[0082] (2) From 40°C to 35°C, the cooling curve becomes gentle. At this time, the paraffin phase changes and releases heat, releasing the heat absorbed during high-temperature heat storage, delaying the temperature drop of the material. Through the phase transition of endothermic melting and exothermic solidification, full utilization of heat is achieved. In this exothermic process, the exothermic phase change duration of Examples 1, 4, and 5 corresponds to the endothermic duration. Due to the difference in wax content, the exothermic duration is also significantly different. The exothermic durations of the three are 82 min, 95 min, and 72 min, respectively.
[0083] (3) 35℃~25℃, the paraffin has solidified, and the temperature of the phase change material gradually decreases to the same temperature as the constant temperature box.
[0084] Low temperature cold storage process: Figure 6 The temperature change curves of the low-temperature cold storage and cold release experiments of Examples 1, 4, and 5 are shown in the table above. It can be seen that the energy storage materials of Examples 1, 4, and 5 with different moisture contents of 10, 20, and 30 wt.% have a cooling and cold storage process of 25°C to -20°C divided into three stages:
[0085] (1) 25°C to the cold storage phase transition temperature (-8.4°C for Example 1, -12.1°C for Example 4, and -7.8°C for Example 5), that is, before the temperature drops to the water crystallization phase transition temperature of the energy storage material of the embodiment, the temperature of the material drops rapidly;
[0086] (2) Cold storage phase transition temperature ~ cold storage phase transition temperature, the water content of the energy storage materials in the three embodiments is different, and the corresponding water crystallization supercooling is also different. Figure 5 It can be found that with the increase of water content, the water crystallization phase transition temperature of the embodiment also gradually increases, which shows that the water content can improve the water crystallization supercooling, promote the crystallization of water droplets at a higher temperature, and store cold energy in solid ice. In addition, in the cold storage stage, the maximum temperature of the 30wt.% water-containing energy storage material of Example 5 is -2.8°C, and the crystallization cold storage time is 25min (the time from -7.8°C at the beginning of the phase change to the time when the material is cooled to -7.8°C again); the 20wt.% water-containing energy storage material of Example 1 is The highest temperature is -5.5°C, and the crystallization cold storage time is 16 minutes (the time from -8.4°C when the phase change starts to the time when the material cools down to -8.4°C again); while the highest temperature of -12°C of the 10wt.% water-containing energy storage material with the lowest moisture content in Example 4 is almost the same as the cold storage phase change temperature of -12.1°C, and the crystallization cold storage time is only 7.5 minutes. This shows that the higher the moisture content, the greater the low-temperature cold storage energy storage density of the phase change material, and the higher energy storage density makes the reverse temperature rise of the material higher and the cold storage time longer. Taking into account the temperature and duration of both heat storage and cold storage of the energy storage material, combined with Table 1 and Table 2, Example 1 balances the requirements of temperature and duration for heat storage and cold storage.
[0087] (3) The phase change temperature of cold storage is ~ -20°C. After the water phase completes crystallization and cold storage, the temperature of the phase change material drops to the ambient temperature of -20°C.
[0088] The process of heating and cooling from -20℃ to 25℃ is divided into three stages:
[0089] (1) -20°C to 0°C, the temperature of the phase change energy storage materials of Examples 1, 4, and 5 all rises rapidly, and the ice does not melt and release cold at this time;
[0090] (2) 0℃~0℃, similar to supercooling, the phase change energy storage materials prepared with three different water contents all showed ice melting endothermic phenomenon at 0℃. At this time, the temperature of the material no longer changed, which showed that the cold energy stored in water crystals was released to the environment. During the cold release process, there was no obvious difference in the cold release temperature between different water contents, but the cold release time was not the same. Specifically, the cold release time of the energy storage material with a water content of 10wt.% in Example 4 was 6min, the cold release time of the energy storage material with a water content of 20wt.% in Example 1 was 16min, and the cold release time of the energy storage material with a water content of 30wt.% in Example 5 was 31min, which shows that the higher the water content, the higher the cold release of the water phase, showing a better storage capacity.
[0091] (3) 0℃~25℃, after the water phase cold storage is completely released, the temperature of the material continues to rise until it reaches the same as the ambient temperature of 25℃.
[0092] Comparative Example 1
[0093] 100wt.% paraffin wax with a phase change temperature of 40°C is placed in a high-temperature heating box, heated to 75°C and kept at a constant temperature for 30 minutes, then placed in a 25°C constant temperature box to cool down, and finally a typical paraffin wax phase change heat storage material is prepared.
[0094] Conventional paraffin-based phase change energy storage materials mostly only consider the material heat storage process, that is, only paraffin is used as the phase change material.
[0095] Comparative Example 2
[0096] The difference between this comparative example and Example 1 is that the addition amount of deionized water is adjusted to 5 wt.%, and the rest of the preparation process is the same as that of Example 1 to obtain a phase change energy storage material.
[0097] Comparative Example 3
[0098] The difference between this comparative example and Example 1 is that 20 wt.% of water phase is completely added into the solution of liquid paraffin and Span80 surfactant at one time, and the rest of the preparation process is the same as that of Example 1 to obtain a phase change energy storage material.
[0099] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 3.
[0100] Table 3
[0101] Moisture content Endothermic phase transition temperature Exothermic phase transition temperature Cold storage phase change temperature Phase transition temperature Example 1 20wt.% 35℃ 40℃ -8.4℃ 0℃ Comparative Example 1 0wt.% 35℃ 40℃ / / Comparative Example 2 5wt.% 35℃ 40℃ -18.5℃ 0℃
[0102] As can be seen from the above table, compared with Example 1, Comparative Example 1 contains only one phase change material, paraffin, and there is no water phase change involved, so it cannot achieve the low-temperature cold storage function, that is, there is no corresponding cold storage / cold release phase change temperature, and it can only achieve a single high-temperature heat storage function. Compared with Example 1, Comparative Example 2 has a water content of 5wt.%, which is less than the 20wt.% water content of Example 1. Due to the low water content, after the water phase is emulsified into small water droplets, the crystallization supercooling of water is large, which is manifested as a cold storage phase change temperature of -18.5°C, which is closer to the ambient temperature of -20°C, indicating that the material of Comparative Example 2 has a serious lag in response to low-temperature cold storage.
[0103] In addition, in Comparative Example 3, the phase change energy storage material was prepared by adding water once. In the subsequent heat storage experiment, it was found that after the material was heated from 25°C to 60°C and cooled from 60°C to 25°C, the water phase separated from the emulsion. Figure 1 At the bottom of Example 1 shown, larger water droplets and even partially transparent liquid water appeared. The reason is that too much water was added at one time. Compared with the staged water addition in Example 1, the water phase was emulsified by the surfactant into water droplets with larger particle size. After the material was heated at high temperature, flocculation and aggregation occurred between the water droplets to form larger water droplets, which precipitated from the paraffin and deposited at the bottom of the material. The stability of the material in Comparative Example 3 is poor.
[0104] In summary, the present invention fully utilizes the latent heat of phase change of paraffin and water, realizes the comprehensive utilization of both heat and cold energy, and enriches the levels and methods of energy storage and utilization.
[0105] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage, characterized in that: Calculated by mass percentage, the composition comprises 65-89wt.% of paraffin-based phase change material, 10-30wt.% of liquid water phase, and 1-5wt.% of oil-soluble surfactant.
2. The phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage as claimed in claim 1, characterized in that: The paraffin-based phase change material includes normal alkane paraffin, isoalkane paraffin or a mixture of normal and isoalkane paraffins with different carbon chain lengths.
3. The phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage as claimed in claim 1, characterized in that: The oil-soluble surfactant includes one or more of Span 60, Span 80, and glyceryl monostearate.
4. The phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage as claimed in claim 1, characterized in that: The phase change temperature of the paraffin-based phase change material from solid to liquid is 35-40° C., and the phase change latent heat is 155-165 kJ / kg.
5. A method for preparing a phase change energy storage material capable of storing both high-temperature heat and low-temperature cold according to any one of claims 1 to 4, characterized in that: include, The paraffin-based phase change material is heated to 70-75° C. and then kept at a constant temperature for 20-40 minutes. After the material is completely melted, a surfactant is added and the material is heated for 5-7 minutes to obtain a liquid mixture. After the liquid mixture is stirred at a speed of 200 to 250 r / min and cooled to 50±1°C, deionized water is added and the stirring speed is adjusted to 600 to 700 r / min to promote the dispersion of the water phase into micro-nano-scale water droplets in the liquid paraffin. After the water phase is added, the mixture is stirred for 10 to 12 minutes; After the stirring is completed, the temperature is cooled down and the paraffin is completely solidified, and finally a phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage is obtained.
6. The method for preparing a phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage as claimed in claim 5, characterized in that: The water is added to the liquid paraffin by a combination of dropwise addition and emulsification, including: Divide the water into 4 to 6 equal portions by volume, take one portion and slowly add it dropwise into the paraffin. After the addition is completed, allow the water phase to fully emulsify in the liquid paraffin for 1 to 2 minutes. Repeat this process until the water sample is completely added to the liquid paraffin.
7. The method for preparing a phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage as claimed in claim 6, characterized in that: During the dropping and emulsifying process, the liquid paraffin is kept in a stirring state.
8. The method for preparing a phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage as claimed in claim 6, characterized in that: The temperature of the deionized water is consistent with that of the liquid mixture.
9. The method for preparing a phase change energy storage material that takes into account both high-temperature heat storage and low-temperature cold storage as claimed in claim 5, characterized in that: The cooling temperature is 25±0.5°C.